Procompetitive Trade Policies - José Luis Moraga Gonzales; Jean-Marie Viaene (Center for Economic Studies and ifo Institute (CESifo), 2001)
We study the procompetitive effects of trade policies against a foreign oligopoly in a model of vertical product differentiation. We show that a uniform tariff policy like the Most Favored Nation (MFN) clause is always welfare superior to free trade because of a pure rent-extraction effect. However, a nonuniform tariff policy is, in addition, procompetitive and thus yields a higher level of social welfare. The first best policy typically consists of giving a subsidy to the country producing low quality and levying a tariff on the country producing high quality. Regional Trade Agreements (RTYs) are examples of nonuniform tariff policies. We show that these arrangements yield higher welfare than free trade and, moreover, that a RTA with a low-quality producing country yields larger gains than a RTA with a high-quality producing country.
Keywords: 330; endogenous quality; most favored nation (MFN) clause; procompetitive policies; regional trade agreements